Avaliação dos mecanismos de Privacidade e Personalização na Web - Lobato, Luanna Lopes (Universidade Federal de São Carlos, 2007)
In web services two points should be considered that end up conflicting: i) the user's right to have his privacy guaranteed and ii) the need of having the services personalized, providing a better user interaction on the Internet. The user's information, with regard to privacy, should be maintained in secrecy, so that the person in question would not feel threatened when using the service. When thinking about personalization, the information should be known and filtered, in a way that makes it possible to discover the most relevant information, so that, together with personalization techniques, they can be used by the sites. This work presents the steps taken for the development of a tool, PrivPerson , capable to analyzing the privacy and personalization mechanisms, being: tools, sites and use sceneries in a way that quantify/measure how much privacy and personalization they offer for the users. For such measurements, a base the taxonomies of classification of privacy and personalization was used, developed in this work and imposed in layers, in a way that it is possible to quantify the privacy and personalization level of offered to the user by the observation of which layers the mechanism meditates. The mechanisms analysis for the proposed tool had the goals to supply the users quantitative values that aid the user in the context of use services. Apart from the above, a Case Study was developed with the objective of identifying the use of the taxonomies on sites, and to compare the manual evaluation on the sites, done in the Case Study, with the automated evaluation found in PrivPerson . With base in this study, it was observed that the sites doesn't have a standardization in the development of their Privacy Politics, based on this, a standardization was developed for such politics, approaching information that are relevant be introduced to the users by the sites.
Keywords: Privacidade e personalização; Internet (Redes de computação); Word wide web - medidas de segurança; Privacy; Personalization; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO